Studies of Mast Cells: Adventures in Serendipity - Brown, Melissa A. (Frontiers in Immunology, 2018)
Like many of us who had the great fortune to work with Bill Paul, my science life was immeasurably altered by my interactions with him. Although intimidating at first because of his stature in the immunology world, it was soon clear that he not only truly cared about the specific research we were doing together, but he wished to convey to his trainees an approach to science that was open, always questioning, and infinitely fun. His enthusiasm was infectious and after my training with him, despite stresses due to funding and publishing hurdles, I never regretted the path I took. My research took a sharp turn from the studies of adaptive immunity I had planned on pursuing after my fellowship with Bill to a life long quest to understand the wonders of the mast cell, a relatively rare innate immune cell. This came about because Bill’s curiosity and expectation of the unexpected allowed him to view, in retrospect, a rather mundane observation we made together involving a non-physiological transformed mast cell line as something that might be really interesting. I have never forgotten that lesson: Look at the data with an eye on the big picture. Sometimes the unexpected is more interesting than predicted results. His example in this regard was incredibly important when as an independent investigator a mistake in mouse sex determination led to unexpected and very confusing data. Yet, these data ultimately revealed a role for mast cells in male-specific protection in experimental autoimmune encephalomyelitis, the mouse model of multiple sclerosis. Bill’s influence in immunology is far-reaching and will continue to be felt as those of us who train our own students and post-doctoral fellows pass on his wisdom and approach to scientific research.